Literasi Akad Dan Produk Perbankan Syariah Di SMA Negeri 1 Muara Badak Kabupaten Kutai Kartanegara - Rinna Ramadhan Ain Fitriah; Nurfiza Widayati; Akbar Lufi Zulfikar; Swadia Gandhi Mahardika (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to provide literacy and knowledge about Islamic banking contracts and products to the students of SMA Negeri 1 Muara Badak, Kutai Kartanegara Regency. This activity is carried out as a form of community service by the Sharia Economics Program of the Faculty of Economics and Business, Mulawarman University. The program lasted for three days, involving seminars and interactive discussions on the principles, contracts, and products offered by Islamic banking. The results of the activity showed an increase in participants' understanding and awareness of the importance of choosing financial institutions that comply with Islamic law, as well as the differences between Islamic and conventional banking. Recommendations include the need for deeper financial education, the use of technology in Islamic financial literacy, and the active role of teachers and parents in strengthening this knowledge.